2017
DOI: 10.1111/iju.13336
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms/benign prostatic hypertrophy and vascular function: Role of the nitric oxide–phosphodiesterase type 5–cyclic guanosine 3′,5′‐monophosphate pathway

Abstract: It is well known that there is an association of lower urinary tract symptoms/ benign prostatic hypertrophy with cardiovascular disease, suggesting that lower urinary tract symptoms/benign prostatic hypertrophy is a risk factor for cardiovascular events. Vascular function, including endothelial function and vascular smooth muscle function, is involved in the pathogenesis, maintenance and development of atherosclerosis, leading to cardiovascular events. Vascular dysfunction per se should also contribute to lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 195 publications
(425 reference statements)
0
4
0
1
Order By: Relevance
“…Regarding the vascular endothelium, the key contributor to the androgen vasorelaxation effect is controversial. Some studies demonstrated that vascular endothelium has a major role in the T vasodilator mechanism [26,27], depending on species and gender. On the contrary, others demonstrated that this effect may occur through an independent-endothelium pathway [28][29][30], by direct action of T on the vascular smooth muscle.…”
Section: Genomic and Non-genomic Overlapping Vasodilatory Mechanisms mentioning
confidence: 99%
“…Regarding the vascular endothelium, the key contributor to the androgen vasorelaxation effect is controversial. Some studies demonstrated that vascular endothelium has a major role in the T vasodilator mechanism [26,27], depending on species and gender. On the contrary, others demonstrated that this effect may occur through an independent-endothelium pathway [28][29][30], by direct action of T on the vascular smooth muscle.…”
Section: Genomic and Non-genomic Overlapping Vasodilatory Mechanisms mentioning
confidence: 99%
“…Similar to TRP channels, the activation of mechanosensitive channels such as Piezo1 114 can also result in enhanced microglial migration (Fig. 2) via cytoskeleton remodeling [116][117][118][119][120] .…”
Section: Discussionmentioning
confidence: 99%
“…The PDE5-Is have been reported to exert strong pharmaceutical effects for smooth muscle relaxant in bladder neck and prostatic urethra [ 9 , 18 , 19 ], vasodilatation response in lower urinary tract (LUT) [ 7 , 20 ], inhibition of bladder afferent nerve activity [ 21 ] and reduction in prostatic inflammation related with LUTS [ 8 ]. Although the functional role of PDE5 remains controversial, a main stream is NO/cGMP signaling pathway in the crosstalk between efferent nerve terminal and LUT smooth muscle cell, or endothelial and vessel smooth muscle cell [ 22 ]. Previous reports revealed that expression of PDE5 is robust in endothelial and smooth muscle cells of LUT vessels, and tadalafil plays a critical role in vasodilatation of vesicular-differential artery via inhibition of cGMP degradation by blocking of PDE5 activity [ 6 , 23 ].…”
Section: Discussionmentioning
confidence: 99%